Atualizações na utilização do IL-1Ra no tratamento de artrite em equinos - Ferrari, Lorena Cardozo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In the equine clinic, locomotor diseases have great prominence in the series, among them osteoarthritis (OA) is becoming increasingly common in equine breeding. Degeneration and enzymatic degradation, the result of biologically complex processes, follow the loss of articular cartilage and are recognized as major triggers for the development of joint diseases. The metacarpophalangeal joint is the most affected by spontaneous OA, followed by the carpal joint, due to the weight they support and the great impact during exercise. The studies began in the human species, but soon there was the perception of similarity with horses, this is what led to the development of comparative studies between the two species. As an important cause of pain, claudication, economic loss, early retirement and loss of performance for athletes, the search for treatment is increasingly encouraged. One of the treatment approaches that has gained prominence is the use of cytokine inhibitors, among them the cytokine with great impact on the inflammatory process is interleukin 1. Therefore, the interleukin 1 receptor agonist (IL- 1Ra), an anti-inflammatory inflammation naturally produced in an inflammation, can be explored in research and used to reduce cartilage degeneration

Na clínica equina, as enfermidades locomotoras têm grande destaque na casuística, dentre elas a osteoartrite (OA) se torna cada vez mais comum nas criações de equinos. A degeneração e degradação enzimática, resultado de processos biologicamente complexos, sucedem a perda da cartilagem articular e são reconhecidas como grandes gatilhos para desenvolvimento de doenças articulares. A articulação metacarpofalangeana é a mais acometida por OA espontânea, seguida pela articulação do carpo, devido ao peso que sustentam e ao grande impacto durante o exercício. Os estudos se iniciaram na espécie humana, mas logo ocorreu a percepção da similaridade com os equinos, isso foi o que levou ao desenvolvimento de estudos comparados entre as duas espécies. Sendo uma importante causa de dor, claudicação, perda econômica, aposentadoria precoce e perda de desempenho para atletas, a busca pelo tratamento é cada vez mais incentivada. Uma das abordagens no tratamento que tem ganhado destaque é o uso de inibidores de citocinas, dentre elas a citocina de grande impacto no processo inflamatório é a interleucina 1. Portanto, o agonista de receptor de interleucina 1 (IL- 1Ra), proteína anti-inflamatória naturalmente produzida em uma inflamação, pode ser explorado em pesquisas e usado para reduzir a degeneração da cartilagem.
Updates on the use of IL-1RA in the treatment of arthritis in horses
Keywords: Horses; Arthritis; Interleukin; Equinos; Artrite; Interleucina